Identification of Subnanometric Ag Species, Their Interaction with Supports and Role in Catalytic CO Oxidation; Molecules; Vol. 21, iss. 4 - Kotolevich Y. Yulia; Kolobova E. N. Ekaterina Nikolaevna; Khramov E. Evgeniy; Cabrera Ortega Jesus Efren; Farias M. H. Mario; Zubavichus Y. Yan; Zanella R. Rodolfo; Mota-Morales J. D. Josue; Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N. Nina; Corberan V. C. Vicente Cortes (2016, 2016)
The nature and size of the real active species of nanoparticulated metal supported catalysts is still an unresolved question. The technique of choice to measure particle sizes at the nanoscale, HRTEM, has a practical limit of 1 nm. This work is aimed to identify the catalytic role of subnanometer species and methods to detect and characterize them. In this frame, we investigated the sensitivity to redox pretreatments of Ag/Fe/TiO2, Ag/Mg/TiO2 and Ag/Ce/TiO2 catalysts in CO oxidation. The joint application of HRTEM, SR-XRD, DRS, XPS, EXAFS and XANES methods indicated that most of the silver in all samples is in the form of Ag species with size <1 nm. The differences in catalytic properties and sensitivity to pretreatments, observed for the studied Ag catalysts, could not be explained taking into account only the Ag particles whose size distribution is measured by HRTEM, but may be explained by the presence of the subnanometer Ag species, undetectable by HRTEM, and their interaction with supports. This result highlights their role as active species and the need to take them into account to understand integrally the catalysis by supported nanometals.